Quantum chemical characterization of the CF2(OH)CF2OONO2 and CF3CF2OONO2 peroxynitrates and related radicals - Delvalle Mongelós, Rosa Isabel (2015)
We present a detailed study of the molecular conformations, vibrational spectra and thermochemistry of the CF2(OH)CF2OONO2 and CF3CF2OONO2 peroxynitrates. In addition, we studied the CF2(OH)CF2OO, CF2(OH)CF2O, CF3CF2OO and CF3CF2O radicals, formed by the rupture of Osingle bondN and Osingle bondO bonds of the above peroxynitrates. The geometric structures of the most stable conformations were determined by density functional theory calculations. At the B3LYP/6-311++G(3df,3pd) level of theory, both peroxynitrates present dihedral angle COON values of about 104°. At the best levels of theory employed, G3(MP2)B3 and G4(MP2), the standard enthalpies of formation at 298 K derived from isodesmic reactions, are −265.6, −248.6 and −248.5 kcal mol−1 for CF2(OH)CF2OONO2, CF2(OH)CF2OO and CF2(OH)CF2O respectively; while for CF3CF2OONO2, CF3CF2OO and CF3CF2O the values of −268.2, −252.6 and −251.9 kcal mol−1 were obtained. Bond dissociation enthalpies of 25.1 and 35.0 kcal mol−1 have been predicted for the first time for CF2(OH)CF2OOsingle bondNO2 and CF2(OH)CF2Osingle bondONO2 and of 23.7 and 34.2 kcal mol−1 have been estimated for CF3CF2OOsingle bondNO2 and CF3CF2Osingle bondONO2. The obtained result of the dissociation enthalpy of CF3CF2OOsingle bondNO2 is in excellent agreement with the available experimental determination. Therefore, the Osingle bondN bond fission is the primary thermal dissociation pathway for both studied peroxynitrates.